(untitled) - Wirthlin, Richard B. (Hoboken, N.J., 2004)
This delightful book delves into the depths of Reagan's character, his ability to communicate with any group, and the reasons for his success in the political world. Warm and personal, it's a tribute to the man Reagan was, both in his public and private moments. I highly recommend it and hope you enjoy it as much as I did.
Keywords: Presidents,Tổng thống,Political consultants,Cố vấn chính trị; Tiểu sử,Tiểu sử; United States,Hoa Kỳ,United States,Hoa Kỳ